HUBUNGAN SPIRITUALITAS DENGAN RESILIENSI PADA DEWASA AWAL PENYINTAS COVID-19 DI JAKARTA - Aldi Kurniadi Christian; Denrich Suryadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
COVID-19 survivors are prone to experience stress, loneliness, anxiety, and other negative emotions that could emerge during the isolation or their treatment period. The role of resilience is very important for COVID-19 survivors to face their situations and heal psychologically. Previous research has shown that there is a correlation between spirituality and resilience in different cases. Jakarta is an area with the highest COVID-19 cases in Indonesia, with majority of the people who were infected are still in their early adulthood. This study aims to find out the correlation between spirituality and resilience in COVID-19 survivors in Jakarta. This study involved 200 samples, obtained by using the non-probability sampling technique. This research used a quantitative approach and adapted versions of the Spirituality Attitude and Involvement List by Meezenbroek et al. (2012) and the Brief Resilience Scale by Smith, et al. (2008). The results of the analysis between the variable spirituality and resilience using Pearson Correlation have a value r = 0.461 and p = 0.000 < 0.05, which means there is a significant positive correlation between spirituality and resilience, which can be concluded that the higher level of spirituality, the higher resilience in COVID-19 survivors.